¨ Valoracion del test findrics como predictor de riesgo de padecer diabetes mellitus ¨ - Andrade Riera, Susan Marcela (2020)
Currently, it finds increasingly higher data regarding the diagnosis of diabetes mellitus. In primary prevention, the diagnostic prediction test is included, and among them, we have FINDRICS, a simple, non-invasive, and inexpensive instrument, from which the available evidence, predictive capacity, and usefulness t were reviewed. He inquired about the worldwide variations that have been made to it. The methodological strategy is based on documentary analysis based on discrimination, ordering, and interpretation of scientific articles. After the initial search, 256 articles were located. Finally, three systematic reviews, ten original studies, and 17 articles related to risk factors and diseases associated with Diabetes Mellitus were selected, in which said the test is also applied. The Findrics Test has shown worldwide epidemiological validity as a reliable instrument in determining the risk of developing Diabetes Mellitus and prediabetes. Since out of 30 articles collected 17 studies will be considered with an AUC between 0.60 and 0.84 that seem to have the functional predictive capacity, 23 Articles recommended the use of the Test Findrics more than half are Latin American countries and in turn, indicate that the need has arisen to adapt to FINDRICS according to the environment of people. Three articles do not recommend FINDRICS, as their models are proposed to predict the risk of diabetes mellitus with an AUC that outperforms compared to FINDRICS.